The Effect of Probiotic Yogurt on Blood Glucose and cardiovascular Biomarkers in Patients with Type II Diabetes: A Randomized Controlled Trial - Mahin Rezaei; Akram Sanagoo; Leila Jouybari; Naser Behnampoo; Ali Kavosi (Mashhad University of Medical Sciences, 2017)
Background: Given the high prevalence of type II diabetes and its complications, the evidence regarding the beneficial effects of probiotic yogurt on some cardiovascular biomarkers in diabetic patients is worthy of investigation. Aim: To investigate the effect of probiotic yogurt on blood glucose level and cardiovascular biomarkers in patients with type II diabetes. Method:This randomized, clinical trial was conducted on 90 patients with type II diabetes who visited the 5 Azar diabetes clinic in Gorgan, Iran, in 2014. The intervention group consumed three 100 g packages of probiotic yogurt per day for four weeks, while the control group used an equal amount of plain yogurt. Dietary intake, as well as anthropometric and biochemical parameters were measured before and after the trial. To analyze the data, independent t-test, paired t-test, and analysis of covariance were performed, using SPSS version 18. Results: The mean ages of the intervention and control groups were 50.49±10.92 and 50.13±9.20 years, respectively. In the intervention group, paired t-test showed significant differences between mean levels of blood glucose, cholesterol, low-density lipoprotein (LDL), triglycerides, diastolic blood pressure, and glycated hemoglobin before and after four weeks of daily intake of probiotic yogurt (P0.05). At the end of trial, the independent t-test showed a significant difference between the two groups in terms of mean levels of blood glucose, LDL, triglycerides, blood pressure, and glycated hemoglobin (P